2011
DOI: 10.1186/1742-2094-8-178
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 signaling is either protective or pathogenic for the development of Theiler's virus-induced demyelinating disease depending on the time of viral infection

Abstract: BackgroundWe have previously shown that toll-like receptor 3 (TLR3)-mediated signaling plays an important role in the induction of innate cytokine responses to Theiler's murine encephalomyelitis virus (TMEV) infection. In addition, cytokine levels produced after TMEV infection are significantly higher in the glial cells of susceptible SJL mice compared to those of resistant C57BL/6 mice. However, it is not known whether TLR3-mediated signaling plays a protective or pathogenic role in the development of demyeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…The DCs treated with the ligands for TLR2, TLR3, TLR4, and TLR7 induced Th17 development significantly and further increased Th1 development, suggesting that signaling functions for the TLRs are similar in these DCs. The upregulated Th17 development in the presence of TLR3 and TLR4 ligands was consistent with the previous reports (18,31). In addition, the effects of a given TLR were consistent with the different TMEV-specific stimulants, such as VP2 peptide, UV-TMEV, and TMEV.…”
Section: B6s Mice Infected With Tmev Do Not Develop Demyelinating DIsupporting
confidence: 79%
See 1 more Smart Citation
“…The DCs treated with the ligands for TLR2, TLR3, TLR4, and TLR7 induced Th17 development significantly and further increased Th1 development, suggesting that signaling functions for the TLRs are similar in these DCs. The upregulated Th17 development in the presence of TLR3 and TLR4 ligands was consistent with the previous reports (18,31). In addition, the effects of a given TLR were consistent with the different TMEV-specific stimulants, such as VP2 peptide, UV-TMEV, and TMEV.…”
Section: B6s Mice Infected With Tmev Do Not Develop Demyelinating DIsupporting
confidence: 79%
“…Our present study (Fig. 7) showed that the Th17 polarization can be achieved equally well in APCs from susceptible and resistant mice with agonists of multiple TLR receptors (TLR2, -3, -4, and -7), which are either known or suspected to be associated with the innate immune responses following TMEV infection (18,26,(29)(30)(31). Therefore, the potential deficiency of the signal induction in any of these TLRs is unlikely to be associated with the differential Th17 polarization.…”
Section: Discussionmentioning
confidence: 82%
“…However, T cells expressing elevated PD-1 levels in HIV-1 infection do not appear to be functionally exhausted (42). Furthermore, we have repeatedly demonstrated that T cells in the CNS of TMEV-infected resistant B6 mice vigorously function for cytolysis and IFN-␥ production (34), yet the majority (ϳ70%) of the T cells express PD-1, similar to functionally compromised T cells in the CNS of infected susceptible SJL mice (Fig. 2).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, there was no impairment in the expression of PD-1 and PDL-1 on macrophages from TLR3 KO mice after in vitro TMEV infection (not shown). Interestingly, type I IFN (IFN-␣ and IFN-␤) and IL-6 levels are higher in TLR3 KO mice than in control mice due to the elevated viral load in the CNS (34). Thus, the elevated levels of type I IFNs caused by high viral loads in TLR3 KO mice may circumvent TLR3-dependent signaling for the induction of type I IFNs and IL-6 (46,47).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation